Operation of an electron-cyclotron-resonance ion source with supplemental electron injection - I. Boscolo; S. Cialdi; S. Gammino; G. Ciavola (Physical Review Special Topics. Accelerators and Beams, 2003)
Experimental observations obtained on an electron-cyclotron-resonance ion source with electron injection by a ferroelectric cathode are presented. The results are in reasonable agreement with the proposed qualitative plasma model based on the Fokker-Planck equation. A procedure for the optimized operation of an ion source with electron injection is presented on the base of the experimental observations.